Is the Perinatal Outcome of Placental Abruption Modified by Clinical Presentation? - Seishi Furukawa; Hiroshi Sameshima; Tsuyomu Ikenoue; Masanao Ohashi; Yoshio Nagai (Hindawi Limited, 2011)
Objective. The purpose of this study was to elucidate the impact of the clinical presentation on perinatal outcome in placental abruption. Study Design. A retrospective study was performed in 97 placental abruptions. Placental abruptions were classified according to clinical presentation: pregnancy-induced hypertension (HT, n=22), threatened premature labor and/or premature rupture of membranes (TPL/ROM, n=35), clinically low risk (LR, n=27), and others (n=13). Perinatal outcomes were compared among the HT, TPL/ROM, and LR groups. Results. The HT had significantly higher incidence of IUGR, IFUD, and low fibrinogen. The TPL/ROM had less severe disease. However, the LR had significantly higher incidence of IUFD, low UA pH < 7.1, low Apgar score of <7 at 5 min, and low fibrinogen. Conclusion. Disease severity in placental abruption is likely to depend on the clinical presentation.